Women's career development throughout the lifespan : an international exploration - Bimrose, Jenny, 1949-; McMahon, Mary, 1955-; Watson, M. B. (Mark Brownlee), 1949- (London : Routledge, 2015)
'Women's careers have been a topic of research and discussion in many disciplines including sociology, business, industrial, organisational and vocational psychology, and career guidance. Despite the introduction of equal employment legislation in many countries, women's patterns of career development continue to reflect structural labour market disadvantage.This unique book brings together expert contributions from academic researchers, as well as representing the voices of older women who participated in an international research investigation. Grounded in multidisciplinary empirical studies, the book provides: a variety of perspectives on women's careers in the 21st century; an international exploration of the voice of the older woman; an understanding of both the challenges and responses to women as they construct their careers.Offering a comprehensive understanding of women's career development throughout the lifespan, this book will be of key interest to academics and researchers from the fields of education, psychology, management, geography, labour market economics and sociology, as well as career practitioners, managers, trainers, researchers and policy developers.'--
Includes bibliographical references and index.
Keywords: Women -- Vocational guidance; Career development; Women -- Employment